2012
DOI: 10.1152/ajplung.00208.2011
|View full text |Cite
|
Sign up to set email alerts
|

The presence of LPS in OVA inhalations affects airway inflammation and AHR but not remodeling in a rodent model of asthma

Abstract: Tsuchiya K, Siddiqui S, Risse P-A, Hirota N, Martin JG. The presence of LPS in OVA inhalations affects airway inflammation and AHR but not remodeling in a rodent model of asthma. Am J Physiol Lung Cell Mol Physiol 303: L54 -L63, 2012. First published April 20, 2012 doi:10.1152/ajplung.00208.2011 is the most frequently used allergen in animal models of asthma. Lipopolysaccharide (LPS) contaminating commercial OVA may modulate the evoked airway inflammatory response to OVA. However, the effect of LPS in OVA on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 43 publications
2
28
2
Order By: Relevance
“…[15][16][17] Interestingly, and for reasons as yet unclear, eosinophils recruited in response to ova sensitization and challenge do not respond in an analogous fashion to PVM. Although both ova and Af promote eosinophil recruitment when administered via the standard sensitization and challenge protocol, ova is otherwise inert (save for potential contamination with lipopolysaccharide 36 ), whereas Af extract is a complex mix of antigens including those that can signal via Toll-like receptors (TLRs) 2 and 4 expressed on bone marrow dendritic cells, macrophages, lung epithelial cells, [37][38][39] and conceivably eosinophils. 40 Zimmermann et al 41 compared the ova and Af sensitization challenge models directly to one another via DNA microarray; among the 236 transcripts unique to the Af sensitization and challenge model are those encoding several proinflammatory cytokines, including IL-1b, IL-1a, CCL3, and most notably, IL-6, which has already been shown to have an impact on virus-eosinophil interactions.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Interestingly, and for reasons as yet unclear, eosinophils recruited in response to ova sensitization and challenge do not respond in an analogous fashion to PVM. Although both ova and Af promote eosinophil recruitment when administered via the standard sensitization and challenge protocol, ova is otherwise inert (save for potential contamination with lipopolysaccharide 36 ), whereas Af extract is a complex mix of antigens including those that can signal via Toll-like receptors (TLRs) 2 and 4 expressed on bone marrow dendritic cells, macrophages, lung epithelial cells, [37][38][39] and conceivably eosinophils. 40 Zimmermann et al 41 compared the ova and Af sensitization challenge models directly to one another via DNA microarray; among the 236 transcripts unique to the Af sensitization and challenge model are those encoding several proinflammatory cytokines, including IL-1b, IL-1a, CCL3, and most notably, IL-6, which has already been shown to have an impact on virus-eosinophil interactions.…”
Section: Discussionmentioning
confidence: 99%
“…[20] Low dose systemic LPS has similar effects on pulmonary eosinophilia. [30] However, mice lacking lipopolysaccharide binding protein, reportedly mount comparable degrees of eosinophilia in response to OVA challenge to wild type controls, although they do not develop allergen-induced airway hyperresponsiveness. [29] However, the administration of exogenous LPS to OVA challenged C57Bl/6 mice is inhibitory of eosinophilia [20] as is high dose LPS challenge of BALB/c mice [25], indicating that the timing, route of administration, origin and dose of LPS may have important influences on the outcome of the challenge.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study on the BN rat undergoing repeated challenges with LPS-rich and LPS-free OVA demonstrated comparable airway smooth muscle remodeling in the large airways. [30].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the latter ensures a well-controlled and widely accepted model allergen in comparable murine experiments [12,23,33]. In order to exclude any side-effects of any LPS contamination within the employed OVA preparations on S. pneumoniae mediated effects on allergic sensitization, we have used LPS-depleted OVA in our study [34][35][36]. We conclude that in our murine allergy model, an infection with S. pneumoniae near the time of allergen exposure prevents the development of an allergic phenotype in adult mice.…”
Section: Discussionmentioning
confidence: 99%